(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The present paper deals with the capacity issues of the vulnerable communities of Bangladesh where hazards accelerate the persistent situation on social inequalities. Bangladesh is prone to natural disasters and the persistent socio-economic inequalities tend to increase due to the disaster risks. Disaster risks then hinder the opportunities of the vulnerable communities to become resilient. In this research the researcher has used both secondary and primary data. The researcher has mainly used the secondary data to explore the link between disaster risk reduction and social inequalities. Moreover, the researcher has collected the primary data by using the key informant interview method to have insights of the experts who have shared their valuable views on the relationship between the effective DRR strategies and its potential to reduce the existing social inequalities. The result of the research reveals that the lack of capacity of the disaster vulnerable communities of Bangladesh traps them into further poverty where they buffer their loss and damages with their limited resources. In Bangladesh it is the poor who are the victims of socio-economic inequality and suffer worst from natural disasters. This situation of disaster and poverty becomes a cycle of trap in which the poor tend to suffer and becomes vulnerable. DRR strategies do have the potential to have a positive impact in this scenario. Effective DRR strategies might lead to increase the capacity of vulnerable communities of Bangladesh and the communities will be more resilient. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(2), 2021, P 66-77